The Central Portion of Factor H (Modules 10–15) Is Compact and Contains a Structurally Deviant CCP Module - Schmidt, Christoph Q. (Elsevier, 2010)
The first eight and the last two of 20 complement control protein (CCP) modules within complement factor H (fH) encompass binding sites for C3b and polyanionic carbohydrates. These binding sites cooperate self-surface selectively to prevent C3b amplification, thus minimising complement-mediated damage to host. Intervening fH CCPs, apparently devoid of such recognition sites, are proposed to play a structural role. One suggestion is that the generally small CCPs 10–15, connected by longer-than-average linkers, act as a flexible tether between the two functional ends of fH; another is that the long linkers induce a 180° bend in the middle of fH. To test these hypotheses, we determined the NMR-derived structure of fH12–13 consisting of module 12, shown here to have an archetypal CCP structure, and module 13, which is uniquely short and features a laterally protruding helix-like insertion that contributes to a prominent electropositive patch. The unusually long fH12–13 linker is not flexible. It packs between the two CCPs that are not folded back on each other but form a shallow vee shape; analytical ultracentrifugation and X-ray scattering supported this finding. These two techniques additionally indicate that flanking modules (within fH11–14 and fH10–15) are at least as rigid and tilted relative to neighbours as are CCPs 12 and 13 with respect to one another. Tilts between successive modules are not unidirectional; their principal axes trace a zigzag path. In one of two arrangements for CCPs 10–15 that fit well with scattering data, CCP 14 is folded back onto CCP 13. In conclusion, fH10–15 forms neither a flexible tether nor a smooth bend. Rather, it is compact and has embedded within it a CCP module (CCP 13) that appears to be highly specialised given both its deviant structure and its striking surface charge distribution. A passive, purely structural role for this central portion of fH is unlikely.